IMPROVING THE SENSE OF PATRIOTISM IN TEACHERS OF FUTURE PHYSICAL CULTURE ON THE BASIS OF A MODERN APPROACH - Fatxulla Miraxmedov (Web of Journals Publishing, 2025)
This article was used as an indicator of the assessment of upbringing when introducing the "concept of continuous spiritual education" from the criteria and indicators of the development of civil and Patriotic competence of future teachers. As a result, the ability to diagnose the readiness of future teachers to form students ' loyalty to the Motherland has increased. These proposals made it possible to prepare future teachers for educational activities, to develop an active civil position in them.
Keywords: Patriotic consciousness, Patriotic Outlook, moral, civil-Patriotic, military-Patriotic, sports-Patriotic, pedagogy.